Behandlung photographischer Abwässer. Ein Umweltschutzproblem von wirtschaftlicher Bedeutung - W. Grossmann (CHIMIA)
The chemical treatment of photographic effluents (eg. oxydation, precipitation) increases the production costs of photographic laboratories and should therefore be considered only as the last step of a series of measures to abate pollution. The main measures are: Recycling of chemical solutions wherever possible, complete recovery of silver, economic use of water, energy recovery by heat exchangers. A carefully planned package of measures achieves pollution control and increases at the same time the profitability of a photographic laboratory.